2001
DOI: 10.1001/archotol.127.6.629
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inner Hair Cell Loss in Premature Infants and Cochlea Pathological Patterns From Neonatal Intensive Care Unit Autopsies

Abstract: Auditory brainstem response failure among these neonatal intensive care unit infants who died was extremely common in part owing to an unexpected histological alteration, selective inner hair cell loss among premature newborns, that should be detectable uniquely by the ABR testing method. Additional histological patterns suggest more than one cause for neonatal intensive care unit hearing loss. Hair cell loss patterns seem frequently compatible with in utero damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 20 publications
2
47
1
7
Order By: Relevance
“…Embora o JCIH 3,8 não faça referência à prematuridade, isoladamente, como um fator de risco para déficit auditivo, em nosso estudo optamos por verificar esta associação já que algumas investigações relacionam a prematuridade à baixa de audição 14,15,16 . Todavia, embora tenha sido encontrada, na análise univariada, uma proporção significativamente maior de déficit auditivo em crianças prematuras quando comparadas com crianças nascidas a termo, esta variável não permaneceu no modelo final de análise multivariada.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Embora o JCIH 3,8 não faça referência à prematuridade, isoladamente, como um fator de risco para déficit auditivo, em nosso estudo optamos por verificar esta associação já que algumas investigações relacionam a prematuridade à baixa de audição 14,15,16 . Todavia, embora tenha sido encontrada, na análise univariada, uma proporção significativamente maior de déficit auditivo em crianças prematuras quando comparadas com crianças nascidas a termo, esta variável não permaneceu no modelo final de análise multivariada.…”
Section: Resultsunclassified
“…Todavia, embora tenha sido encontrada, na análise univariada, uma proporção significativamente maior de déficit auditivo em crianças prematuras quando comparadas com crianças nascidas a termo, esta variável não permaneceu no modelo final de análise multivariada. Amatuzzi et al 14 realizaram um estudo em que foi testada a audição de recém-nascidos de UTI por meio de audiometria de tronco cerebral (BERA) logo após o nascimento, e foi feita a avaliação histológica dos ossos temporais de 15 não-sobreviventes após a morte. O estudo mostrou que alguns pacientes apresentavam perda de células ciliadas externas, outros de células ciliadas internas, e outros, de ambas.…”
Section: Resultsunclassified
“…Damage to the central nervous system in neonates can be caused by anoxia and hypoxia (21,22). However, the influence of neonatal asphyxia on the inner ear of the neonate has been reported only by a limited number of authors (23). Koyama et al (20) have shown that hypoxia and asphyxia may affect the inner ear and balance in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming a normal distribution of EPSP amplitudes results from the quantal release of neurotransmitter (Fuchs, 2005), then a reduction in the amplitude (or number) of EPSPs would reduce the probability of spike initiation (see Figure 4A). This might occur due to disruption of transmitter-release (possibly mediated by otoferlin deficiency, Roux et al, 2006) or a scattered loss of IHCs (Amatuzzi et al, 2001). Alternatively, an increase in the trigger-level voltage could reduce the probability of EPSPs reaching this critical voltage (see Figure 4B), or, depolarisation of the dendrite itself (possibly from lateral efferent modulation; Brown, 1987) would also reduce the chance of EPSPs generating spikes (see Figure 4C).…”
Section: Role Of Evoked Potentials In Decision-makingmentioning
confidence: 99%